A novel role for relaxin-2 in the pathogenesis of primary varicosis - Adams, Julia; Schott, Sarah (PLOS ONE, 2012)
Background Varicose veins affect up to 40% of men and up to 51% of women. The pathophysiology of primary varicosis is poorly understood. Theories ranging from incompetence of the venous valves to structural changes in the vein wall have been proposed. Methodology/Principal Findings We analyzed the functional state of the intramural smooth muscle cells (n = 14 pairs matched for age and gender) and the expression of relaxin-2 and its receptors RXFP1 and RXFP2 in samples of varicose and healthy great saphenous veins (GSV) (n = 21 healthy GSV; n = 46 varicose GSV). Relaxin-2 and RXFP1 contents were determined in tissue samples (n = 9 samples per group). Pharmacological analyses were performed in a perfusion chamber. Morphometric determination of the nuclear size of the smooth muscle compartment yielded no significant difference in varicose GSV in comparison with the healthy controls. Relaxin-2 and its receptors were expressed in the muscular layer, endothelial cells and in blood vessels contained in the vein wall. Immunohistochemical expression of relaxin-2, RXFP1 and RXFP2 was significantly decreased in varicose GSV. Relaxin-2 and RXFP1 measured by ELISA and Western Blot were decreased in varicose GSV (relaxin-2 ELISA healthy vs. varicose GSV: 12.49±0.66 pg/mg versus 9.12±3.39 pg/mg of total protein; p = 0.01; Student's T-test). Contractions of vein samples induced by cholinergic or adrenergic stimulation were antagonized by relaxin-2. Conclusions/Significance We report that relaxin-2 and its receptors RXFP1 and RXFP2 are expressed in GSV and that their expression is significantly decreased in varicose GSV. Further, we were able to demonstrate a functional pharmacological relaxin-2 system in varicose GSV. Our results suggest a novel role for relaxin-2 in the pathogenesis of primary varicosis, rendering relaxin-2 a novel possible pharmacological agent for the treatment of this widely prevailing venous disease.
Gesehen am 24.04.2018